Metode Ijtihad Komisi Fatwa Majelis Ulama Indonesia - Kuswoyo, Bahet Edi (STAI Bumi Silampari, 2026)
This study aims to analyze the ijtihad methods employed by the Fatwa Commission of the Indonesian Ulema Council (Majelis Ulama Indonesia/MUI) in responding to contemporary legal issues in Indonesia. The background of this research is based on the strategic position of MUI as an authoritative institution that provides legal guidance for Muslims and influences public policy related to Islamic law. The research method used is qualitative research with a library research approach, through descriptive analysis of relevant literature, scientific journals, official MUI fatwa documents, and related legal sources. The findings show that the MUI Fatwa Commission applies several methods of ijtihad, namely istinbat, qiyas, maslahah, and the maqasid al-sharia approach, which are adjusted to Indonesia’s social, cultural, and national legal contexts. The fatwa formulation process is carried out through in-depth study, deliberation, and consideration of public benefit to ensure that the resulting fatwas remain relevant and applicable. This study concludes that MUI’s ijtihad methods play an important role in maintaining the relevance of Islamic law amid social development, technological advancement, and the dynamics of positive law in Indonesia.